If it's not what You are looking for type in the equation solver your own equation and let us solve it.
24n/24=-13/24
We move all terms to the left:
24n/24-(-13/24)=0
We get rid of parentheses
24n/24+13/24=0
We multiply all the terms by the denominator
24n+13=0
We move all terms containing n to the left, all other terms to the right
24n=-13
n=-13/24
n=-13/24
| 24n=-13 | | t^2+2t-78=0 | | 10x+2=-15x+9-2x | | 2y+24=8y | | 2x-5/3=3x-10 | | 2.50m+4=21.50 | | b+27-19=12 | | 4(8y+56)=98 | | 3(8x+16)=120 | | 4(5y+25)=40 | | 4(5y+10)=80 | | 3(7y+35)=42 | | 3(6p^2+7p-5)=0 | | 20-8n=15n= | | 2(3y+6)=30 | | n+4=19-2n= | | 4(7y+35)=56 | | 13k-32=8k+8 | | 2/3x+x=20 | | 2a-14-3a=5 | | 6m^+23m+15=0 | | -4t+-36+6t=3t | | (2c-1)^2=25 | | 11z=8 | | 4(3y+4)=10 | | 9x+7=25+2(5-x) | | -11/3m+1/6m=-7 | | (2c-1)^2-4=21 | | -6(4-v)=-24+6v | | (x-3/4)=2/3(3/2x-9/14) | | 2p/2=14 | | 2v+11=29-v |